Identifying a Convergence between Non-Financial Information and Islamic Accounting for Islamic Decision Usefulness: A Review and Synthesis - Ibnu Qizam (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2020)
This study aims to explore a framework of developing the Islamic decision usefulness (IDU) concept through a review of non-financial information and Islamic accounting under the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) literature for convergence and the extent to which this convergence will inspire future empirical-research opportunities for the increased Islamic decision usefulness (IIDU). Exploring and delineating historically non-financial information literature to be linked with Islamic accounting trends through content analysis, this study suggests that decision usefulness of non-financial information has flourished from being complementary to the strategic role of information, adopting the ideas of creating shared value (CSV), and sustainable value-creation (SVC). To this point, the enhancement of decision usefulness emitted from non-financial information and Islamic accounting literature points to the same pole (convergence), exposing the firms’ relevant-sustainable shared-value for 3Ps (profit, people, and planet) blended with Islamic accounting concepts, whereby welcoming many future empirical-research opportunities for the increased Islamic decision usefulness (IIDU).